SOCIAL CRITICISM IN THE SHORT STORY SCREAMING GRAVES BY KHALIL GIBRAN (A SOCIO-LITERARY ANALYSIS STUDY BY ALAN SWINGEWOOD) - Faruqi Abdurrasyid, Muhammad (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The research is entitled “Social criticism in the short story Screaming Graves by Khalil Gibran (A socio-literary analysis study by Alan Swingewood)”. The aims of this research are: First, to find out the substance of the short story Shurakh al Qubur. Second, to find out the social criticism conveyed by the author in the short story. Third, to find out the relationship between the short story Shurakh al Qubur and the social conditions of Lebanese society. In order to analyze the social criticism in the short story, the researcher used Alan Swingewood's literary sociology theory. Swingewood believes that literary works are a reflection of the social conditions in which they were created. In principle, there are three things related to the sociology of literature, namely first, research that views literary works as social documents in which they are a reflection of the situation at the time the literature was created. Second, research that reveals literature as a reflection of the author's social situation. Third, research that captures literature as a manifestation of historical events and socio-cultural conditions. In this study, researchers used the first perspective, namely literary works as social documents. This research produces first, the substance of the short story Shurakh al Qubur which explains that this short story is the author's criticism of the government which is described through the story between the king and the suspect. Second, criticism of authoritarian leaders in power and criticism of autocratic government systems. Third, social criticism in the short story which reflects the conditions of the Ottoman Empire during the leadership of Sultan Abdul Hamid II. This criticism is represented in the figure of a king who is cruel in punishing his people.